1998
DOI: 10.1177/074873098128999961
|View full text |Cite
|
Sign up to set email alerts
|

A Parallelism between Human Body Temperature and Performance Independent of the Endogenous Circadian Pacemaker

Abstract: A battery of performance tests involving manual dexterity, serial search, and verbal reasoning was given about seven times per day to 2 healthy young male subjects (22 and 25 years of age) involved in separate forced desynchrony studies, each involving several months of temporal isolation. In these studies, the period lengths (denoted T) of the imposed day lengths (sleep/wake and light/dark cycles) were 25.8 and 26.0 h for the 2 subjects. For each subject, the endogenous circadian pacemaker (ECP) failed to ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 23 publications
(31 reference statements)
1
8
0
1
Order By: Relevance
“…Consistent with expectations, prior wake time and the overt CBT rhythm had a robust effect on cognitive throughput on both performance measures. This outcome confirms the well-established relationships found between prior wake time and performance (Johnson et al, 1992;Koslowsky et al, 1992;Pilcher et al, 1996;Wyatt et al, 1999), and the tight coupling of overt CBT and performance (Johnson et al, 1992;Kleitman et al, 1950; Monk et al, 1998;Wright et al, 2002). Neither the amount of NREM S1 and S2 sleep nor SWS elicited an effect in cognitive throughput performance in our study.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with expectations, prior wake time and the overt CBT rhythm had a robust effect on cognitive throughput on both performance measures. This outcome confirms the well-established relationships found between prior wake time and performance (Johnson et al, 1992;Koslowsky et al, 1992;Pilcher et al, 1996;Wyatt et al, 1999), and the tight coupling of overt CBT and performance (Johnson et al, 1992;Kleitman et al, 1950; Monk et al, 1998;Wright et al, 2002). Neither the amount of NREM S1 and S2 sleep nor SWS elicited an effect in cognitive throughput performance in our study.…”
Section: Discussionsupporting
confidence: 94%
“…Also, a circadian component in phase with the rhythm of body temperature is found. Further analysis (Wright et al, 2002) has indicated that core temperature affects mental performance independently of circadian rhythmicity, a conclusion that has been drawn also from studies using the constant routine (Monk & Carrier, 1998).…”
Section: Circadian Rhythms In Self‐rated Subjective Feelings and Mentmentioning
confidence: 85%
“…Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden. Terms & Conditions of access and use can be found at http://www.tandfonline.com/page/termsand-conditions Introduction Circadian variations have been documented in performance of many tasks, such as sensory (Lotze et al 1999), motor (Edwards et al 2007(Edwards et al , 2008Jasper, Ha¨ußler, Baur et al 2009;), reaction time (Wright et al 2002;Blatter et al 2006), time estimation (Campbell et al 2001;Kuriyama et al 2003), arithmetic calculations (Loeb et al 1982), manual speed, serial search and verbal reasoning (Monk and Carrier 1998), and memory and logic reasoning tasks (Folkard and Monk 1980). Performance tends to improve during the day and deteriorate during the night (Colquhoun 1971;Lavie 1980;Carrier and Monk 2000).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%